Maternal stress is associated with higher protein-bound amino acid concentrations in human milk - Juncker, Hannah G.; Naninck, Eva F. G.; van Keulen, Britt J.; Harinck, Jolinda E.; Schipper, Lidewij; Lucassen, Paul J.; van Goudoever, Johannes B.; de Rooij, Susanne R.; Korosi, Aniko (Frontiers in Nutrition, 2023)
Background Maternal stress in the postpartum period affects not only the mother, but also her newborn child, who is at increased risk of developing metabolic and mental disorders later in life. The mechanisms of how stress is transmitted to the infant are not yet fully understood. Human milk (HM) is a potential candidate as maternal stress affects various components of HM, e.g. fat and immunoglobulin concentrations. So far, it is unknown whether maternal stress also affects the amino acids (AAs) in HM, even though this nutrient is of extreme importance to child health and development. The aim of this study was to investigated if and how maternal stress is associated with the AA composition of HM. Methods The Amsterdam Mother’s Milk study is anIn this observational cohort study (Amsterdam, The Netherlands). Lactating women were recruited included in two study groups: a high stress (HS) group; women whose child was hospitalized (n=24), and a control (CTL) group; women who gave birth to a healthy child (n=73). HM was collected three times a day, at postpartum days 10, 17 and 24. Perceived psychological stress was measured using validated questionnaires, while biological stress measures were based on hair, saliva and HM cortisol concentrations. HM protein-bound and free AAs were analyzed by liquid chromatography and compared between groups. Results Maternal perceived stress scores were higher in the HS group (p<0.01). The concentrations of protein-bound AAs in HM were higher in the HS group compared to the CTL group (p=0.028) and were positively associated with HM cortisol concentrations (p=0.024). The concentrations of free AAs did not differ between study groups and were unrelated to cortisol concentrations. Conclusion Findings from this prospective cohort study suggest that early-life nutrition, in particular the amino acid composition of human milk, could play a role in the transmission of stress signals from the mother to her childmaternal stress in the postpartum period is associated with an altered human milk amino acid composition which could play a role in the transmission of maternal stress effects to her child. The physiological implications of these stress-induced changes for infant development await future research.